Semiparmetric methods for the measurement of latent attitudes and the estimation of their behavioural consequences - Richard Spady (Centre for Microdata Methods and Practice (cemmap), 2007)
We model attitudes as latent variables that induce stochastic dominance relations in (item) responses. Observable characteristics that affect attitudes can be incorporated into the analysis to improve the measurement of the attitudes; the measurements are posterior distributions that condition on the responses and characteristics of each respondent. Methods to use these measurements to characterize the relation between attitudes and behaviour are developed and implemented.
Keywords: 330; Faktorenanalyse; Meinungsforschung